(untitled) (Cambridge,New York, 2003)
Essays by leading international researchers on the psychology of social judgments discuss the role of evolutionary, neuropsychological and developmental influences on social judgments, in addition to the role of high-level reasoning processes. The delicate interplay between conscious, rational and unconscious automatic mechanisms is emphasized in determining judgmental outcomes. The implications of recent advances in understanding everyday social judgments in people's personal and working lives are stressed.
Keywords: Social perception,Social interaction,Affect (Psychology),Attitude (Psychology),Nhận thức xã hội,Tác động của xã hội,Thái độ (Tâm lý),Sự ảnh hưởng (Tâm lý)